Perempuan dalam Melaksanakan Mandat Ilahi Menurut Kejadian 1:27-28 - Sarah Wassar (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
AbstractGod gave a divine mandate to humans (women and men) since the beginning of creation is to rulethe world (Genesis 1:27). Women and men were created in the image and likeness of God, equal inGod's presence, and received the same Divine mandate and carried out the Divine mandateaccording to God's commands or will. To find out specifically about women in carrying out Divinemandates, this writing is reviewed theologically using qualitative methods, namely literature orliterature study. Then it is presented in the form of a theological review description.